ANALISIS PENERAPAN STRATEGI BERTAHAN PIZZA HUT INDONESIA & KONDISI LABA PERIODE BERJALAN SELAMA PANDEMI COVID-19 - Wahyudi, Hijrah; Mardiyati, Mardiyati (Jurnal Ekonomi STIEP ( JES ), 2021)
This research is expected to be useful for stakeholders both theoretically and practically in terms of choosing and implementing a survival strategy in order to save the company, especially in times of crisis. To answer the research questions, qualitative data analysis techniques were used which followed the following three stages: Data analysis, drawing conclusions and verification and narrative of analysis results. It can be concluded that the defensive strategy undertaken by PT Sarimelati Kencana, Tbk in the face of the Covid-19 pandemic is appropriate, because it is proven that this strategy can still print positive sales, stable cost of goods sold, positive gross profit, still operating profit positive, and stable operating expenses. However, interest and financial expenses that exceed operating profit are the cause of losses for the franchise holder of the Pizza Hut Indonesia restaurant.From this research, it can be suggested for business people in general to consider and pay careful attention to plans or debt decisions. If the business actor is already in debt, then strengthen the intention and determination to immediately pay off these debts. Good products, good product selling prices, effective promotions, strategic selling locations, and increased sales volume will be in vain when business actors are faced with debt interest expenses that exceed operating profit.